An NIR fluorescent/photoacoustic dual-mode probe of NADPH for tumor imaging. Issue 12 (20th January 2023) - Guan, Liandi; Hu, Wanting; Zuo, Hongzhi; Sun, Hua; Ai, Yongjian; He, Meng-qi; Ma, Cheng; Ding, Mingyu; Liang, Qionglin
Abstract : In this work, we synthesized a novel turn-on probe to monitor NADPH levels in energy metabolism and medication of cancer cells and tumor-bearing mice by NIR fluorescent/photoacoustic bimodal imaging with high sensitivity and selectivity. Abstract : A novel probe was synthesized with a turn-on NIR fluorescent (NIRF)/photoacoustic (PA) response to NADPH, which was successfully applied in both monitoring intracellular NADPH and dual-modal imaging of tumor-bearing mice. It exhibits good potential in studying and understanding the tumor energy metabolism and treatment process related to NADPH.